2016
DOI: 10.1111/jir.12311
|View full text |Cite
|
Sign up to set email alerts
|

Community participation of youth with intellectual disability and autism spectrum disorder

Abstract: The current study highlights individual and environmental factors amenable to intervention that may foster successful community participation among youth with ASD and ID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 69 publications
1
32
0
1
Order By: Relevance
“…Three studies showed a mixed relationship between PA and SF, such as Obrusnikova and Cavalier (2011), who found that PA was associated with social advantages (e.g., opportunity to gain social skills) and disadvantages (e.g., bullying) in youth (M age = 10.64 years) with ASD (↑PA∞ ↓↑ SF). Similarly, it was highlighted by Tint et al (2017) that social demands were both a barrier to and facilitator of PA for youth (M age = 16.63 years) with ASD and intellectual disability (↑SF ∞ ↑↓ PA). Taken together, these 14 studies demonstrated the importance of considering both PA and SF for people with ASD, as some social factors were positively associated with PA and others were negatively associated.…”
Section: Resultsmentioning
confidence: 80%
“…Three studies showed a mixed relationship between PA and SF, such as Obrusnikova and Cavalier (2011), who found that PA was associated with social advantages (e.g., opportunity to gain social skills) and disadvantages (e.g., bullying) in youth (M age = 10.64 years) with ASD (↑PA∞ ↓↑ SF). Similarly, it was highlighted by Tint et al (2017) that social demands were both a barrier to and facilitator of PA for youth (M age = 16.63 years) with ASD and intellectual disability (↑SF ∞ ↑↓ PA). Taken together, these 14 studies demonstrated the importance of considering both PA and SF for people with ASD, as some social factors were positively associated with PA and others were negatively associated.…”
Section: Resultsmentioning
confidence: 80%
“…This is not particularly surprising given that there are limited costs to enrolment in SO, which is a not‐for‐profit largely implemented by volunteers, and thus finances would not pose a considerable challenge to register. The presence of enabling factors beyond finance suggests that even within this context, programmes should pay attention to potential barriers, including those that may be present in social settings, in the environment, in transportation, in scheduling or in activity demands (Anaby et al ., 2013; Tint, Maughan, & Weiss, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Informed by results of qualitative interviews with parents [19], the PEM-CY was tested primarily with 576 parents of children with and without disability from Canada and the USA [18] and was found to have moderate to good reliability and validity. The PEM-CY has been used to measure participation of children with specific diagnoses, such as unilateral cerebral palsy [20] and autism spectrum disorder [21], to compare participation of children with different disabilities [22] and between different settings such as home, school and community [23]. The PEM-CY has been translated and culturally adapted into a number of languages, including Korean [16], Chinese [24], Icelandic [21], Hindi (Roopa Srinivasan, personal communication), Dutch (Eftje Kern, personal communication), and Flemish (Mareike Coussens, personal communications).…”
Section: Introductionmentioning
confidence: 99%